SOME RESULTS ON PRIVATE GENETICS OF WHEAT (Experimental biology, 2016)
Genes of traits beneficial for selection were localized on specific donor wheat chromosomes with the use of chromosome engineering. Based on methods of distant hybridization and intervarietal chromosome substitution displaced lines close to analogue and alien substitututed lines were obtained.
Keywords: wheat; leaf rust; gen; localization; identification.